2014
DOI: 10.1080/14763141.2014.909527
|View full text |Cite
|
Sign up to set email alerts
|

Effects of treadmill running and fatigue on impact acceleration in distance running

Abstract: The effects of treadmill running on impact acceleration were examined together with the interaction between running surface and runner's fatigue state. Twenty recreational runners (11 men and 9 women) ran overground and on a treadmill (at 4.0 m/s) before and after a fatigue protocol consisting of a 30-minute run at 85% of individual maximal aerobic speed. Impact accelerations were analysed using two lightweight capacitive uniaxial accelerometers. A two-way repeated-measure analysis of variance showed that, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(87 citation statements)
references
References 35 publications
3
78
0
6
Order By: Relevance
“…In order to control better the running conditions (speed, slope and hardness of the running surface, air resistance, the environment conditions), participants ran on a treadmill. In this sense, previous studies have showed that running on a treadmill is representative although it is not equal to running overground (García-Pérez et al, 2014Riley et al, 2008). Moreover, the effects of this type of garments in different environments (cold or hot) could also be of great interest.…”
Section: Discussionmentioning
confidence: 96%
“…In order to control better the running conditions (speed, slope and hardness of the running surface, air resistance, the environment conditions), participants ran on a treadmill. In this sense, previous studies have showed that running on a treadmill is representative although it is not equal to running overground (García-Pérez et al, 2014Riley et al, 2008). Moreover, the effects of this type of garments in different environments (cold or hot) could also be of great interest.…”
Section: Discussionmentioning
confidence: 96%
“…Second, this review was restricted to non-incline, shod, non-fatigued motorized MT and constant-velocity running below 25 km/h in healthy adults. Biomechanical differences are likely larger when accelerating [100,101] and when running at higher speeds (i.e., sprinting) on regular MT's [17,21] and may also be impacted by the use of shoes [41] and fatigue status [57,58] and the findings of this review can therefore not be generalized to these conditions. Indeed, special MTs have been developed for sprinting that may reduce biomechanical differences [102][103][104].…”
Section: Limitations and Future Directionsmentioning
confidence: 92%
“…In the second and third running tests participants ran on a treadmill (TechnogymSpA, Gambettola, Italy) wearing the assigned garment for that session (GCS or Placebo). These 2 tests followed the same protocol: participants warmed up at selfselected pace for 10 min (which also served as familiarization time on the treadmill [17]), and subsequently performed a 30-min run at 80 % of their MAS. Impact acceleration parameters were measured during 15 s (in order to reduce the measurement error due to stride variability [2]) every 5 min (0′, 5′, 10′, 15′, 20′, 25′, 30′).…”
Section: Experimental Designmentioning
confidence: 99%